Perancangan Key Performance Indicator Departemen Logistik di PT. X - Philip Nathaniel; I Gede Agus Widyadana; Nova Sepadyati (Jurnal Titra, 2021)
PT. X is a manufacturing company that manufactures bikes. One of the departments in PT. X is logistics department that has responsibilities to store, prepare, stuffing, and/or send the product to the customer. The problem faced by the logistics department in PT. X is that the logistics department that consists of three warehouses, logistics analyst, and a team leader only has one Key Performance Indicator (KPIs) for only one warehouse. Moreover, some of these KPIs are not related to logistics department activities and achievement of many KPIs related to performance from two or more departments. These problems make performance measurement of logistics department is not accurate. The purpose of this research is to design Key Performance Indicators that are the full responsibility of logistics department of PT. X based on Business Model Canvas (BMC), quality objectives, and strategy map of the logistics department. BMC, quality objectives, and strategy map is established based on vision, mission, and quality policy of PT. X.